La práctica pedagógica: un espacio de formación para futuros formadores - Muñoz Galíndez, Efraín (Universidad Santiago de Cali, 2020)
The present document contains a reflective exercise of pedagogical practices; topic in the formative process of the future education professionals. The initiative to write on this topic is the result of conversations and dialogues among colleagues due to the importance they have in the training of students and in the curriculum of the Bachelors Education Program in Early Childhood of the Education Faculty of the Corporación Universitaria Autónoma del Cauca (Popayán). A theoretical discussion of concepts, related to the central theme, is performed in the development of the text. Subsequent to it, a trainer of trainers' reflection, on the professional practice, is shown. Finally, to conclude, some considerations from different purviews regarding the practice process are posed, in order to comprehend them from some other approaches.